Early Use of the Palliative Approach to Improve Patient Outcomes in HIV Disease: Insights and Findings From the Care and Support Access (CASA) Study 2013-2019. (April 2021) - Alexander, Carla S.; Raveis, Victoria H.; Karus, Daniel; Carrero-Tagle, Monique; Lee, Mei Ching; Pappas, Gregory; Lockman, Kashelle; Brotemarkle, Rebecca; Memiah, Peter; Mulasi, Ila; Hossain, Basile Mian; Welsh, Christopher; et al.
Young men of color who have sex with men (yMSM) living with human immunodeficiency virus (HIV) in syndemic environments have been difficult-to-retain in care resulting in their being at-risk for poor health outcomes despite availability of effective once-daily antiretroviral treatment (ART). Multiple methods have been implemented to improve outcomes for this cohort; none with sustainable results. Outpatient HIV staff themselves may be a contributing factor. We introduced multidisciplinary staff to the concept of using a palliative approach early (ePA) in outpatient HIV care management to enable them to consider the patient-level complexity of these young men. Young MSM (18-35 years of age) enrolled in and cared for at the intervention site of the Care and Support Access Study (CASA), completed serial surveys over 18 months. Patients' Global and Summary quality of life (QoL) increased during the study at the intervention site (IS) where staff learned about ePA, compared with patients attending the control site (CS) (p=.021 and p=.018, respectively). Using serial surveys of staff members, we found that in the era of HIV disease control, outpatient staff are stressed more by environmental factors than by patients' disease status seen historically in the HIV epidemic. A Community Advisory Panel of HIV stakeholders contributed to all phases of this study and altered language used in educational activities with staff members to describe the patient cohort.